Automatic balancing mechanisms for mixed pension systems under different investment strategies. Issue 2 (11th February 2020) - Boado-Penas, María del Carmen; Godínez-Olivares, Humberto; Haberman, Steven; Serrano, Pedro
Abstract : State pension systems are usually pay-as-you-go financed, i.e. current contributions cover pension expenditure. However, some countries combine funding and pay-as-you-go (PAYG) elements within the first pillar. The aim of this paper is twofold. First, using nonlinear optimisation based on [Godínez-Olivares, H., M. C. Boado-Penas, and S. Haberman. 2016. "Optimal strategies for pay-as-you-go pension finance: A sustainability framework." Insurance: Mathematics and Economics 69: 117–126], it seeks to assess the impact of a compulsory funded defined contribution (DC) pension scheme that complements the traditional defined benefit (DB) PAYG on the level of pension benefits. Future expected returns for both the funded part and the buffer fund of the PAYG are simulated through the non-overlapping block bootstrap technique. Second, in the case of partial financial sustainability, we design different optimal strategies, that involve variables such as the contribution rate, age of retirement and indexation of pensions, to restore the long-term financial equilibrium of the system. We show that the adjustments needed to ensure sustainability for the mixed pension systems are less severe than the pure DB PAYG but the total replacement rate for the former is lower in most of the cases studied. When calculating the return that the individuals would receive, we prove that some cohorts are better off under a mixed pension system.